Self Efficacy Associated with Academic Boredom among Adolescent Santri: Efikasi Diri yang Berkaitan dengan Kebosanan Akademik di Kalangan Remaja Santri - Abdul Aziz; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic boredom is a negative emotional condition frequently experienced in educational environments and is associated with reduced engagement and learning difficulties. Specific Background: Students in Islamic boarding schools often encounter dense and repetitive academic and daily activities, potentially contributing to academic boredom among adolescent santri at Al Fattah Sidoarjo. Knowledge Gap: Previous studies have examined self-efficacy and academic boredom across different educational contexts; however, limited research specifically investigates this relationship among junior and senior high school santri within Islamic boarding school settings using correlational analysis. Aims: This study aims to examine the relationship between self-efficacy and academic boredom among adolescent santri at Al Fattah Sidoarjo. Results: Using a quantitative correlational design, data were collected from 183 santri selected through proportionate stratified random sampling. Measurement utilized Likert-based psychological scales with reliability values of 0.880 for self-efficacy and 0.850 for academic boredom. Pearson product-moment correlation analysis revealed a significant negative relationship between self-efficacy and academic boredom (r = -0.231; p = 0.002). Most participants demonstrated moderate levels of both self-efficacy and academic boredom. Novelty: This study provides empirical evidence of the association between self-efficacy and academic boredom among santri across multiple educational levels within a boarding school context. Implications: The findings suggest the importance of developing programs targeting self-efficacy development and instructional strategies to address academic boredom and support student learning experiences in Islamic boarding schools. Highlights: Higher Confidence in Personal Academic Capability Corresponds With Reduced Learning Fatigue Tendencies. Majority of Participants Demonstrated Moderate Psychological Competence and Learning Disengagement Levels. Statistical Testing Confirmed a Significant Inverse Association Between the Examined Variables. Keywords: Self-Efficacy, Academic Boredom, Adolescent Santri, Islamic Boarding School, Correlational Study